2021
DOI: 10.1001/jama.2021.15494
|View full text |Cite|
|
Sign up to set email alerts
|

Spontaneous Abortion Following COVID-19 Vaccination During Pregnancy

Abstract: Role of the Funder/Sponsor: The funder had no role in the design and conduct of the study; collection, management, analysis, and interpretation of the data; preparation, review, or approval of the manuscript; and decision to submit the manuscript for publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
164
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 177 publications
(180 citation statements)
references
References 6 publications
13
164
1
2
Order By: Relevance
“… 85 Another study including 105,466 pregnancies showed that 8.0% of women with ongoing pregnancies had received a mRNA COVID-19 vaccine in the prior 28 days relative to an index date vs 8.6% of spontaneous abortions and the spontaneous abortions were not associated with an increased odds of COVID-19 vaccine exposure compared with ongoing pregnancies (adjusted odds ratio 1.02; 95% CI 0.96-1.08). 86 Emerging data continues to show that COVID-19 vaccination (including BNT162b2 and mRNA-1273) in pregnant women is safe, effective, and immunogenic, allowing transfer of antibodies to the neonates. 87 , 88 , 89 In August 2021 the CDC recommended COVID-19 vaccination for pregnant women.…”
Section: Clinical Data Of Mrna Therapeutics For Sars Cov-2mentioning
confidence: 99%
“… 85 Another study including 105,466 pregnancies showed that 8.0% of women with ongoing pregnancies had received a mRNA COVID-19 vaccine in the prior 28 days relative to an index date vs 8.6% of spontaneous abortions and the spontaneous abortions were not associated with an increased odds of COVID-19 vaccine exposure compared with ongoing pregnancies (adjusted odds ratio 1.02; 95% CI 0.96-1.08). 86 Emerging data continues to show that COVID-19 vaccination (including BNT162b2 and mRNA-1273) in pregnant women is safe, effective, and immunogenic, allowing transfer of antibodies to the neonates. 87 , 88 , 89 In August 2021 the CDC recommended COVID-19 vaccination for pregnant women.…”
Section: Clinical Data Of Mrna Therapeutics For Sars Cov-2mentioning
confidence: 99%
“…Our study found no evidence of an increased risk for early pregnancy loss after Covid-19 vaccination and adds to the findings from other reports supporting Covid-19 vaccination during pregnancy. 3 , 4 …”
mentioning
confidence: 99%
“…approximately 172,000 to patients who were pregnant at the time of vaccination. Several studies have shown that the COVID-19 mRNA vaccine does not cause early pregnancy loss (before 20 weeks), 8,9 data on other potential effects of the vaccine in pregnancy remain limited but reassuring. 4 Three main tracking systems (CDC Covid-19 Vaccine Pregnancy Registry, Vaccine Safety Datalink (VSD) and Vaccine Adverse Reporting System (VERS)), have not identified increased maternal or fetal risk with COVID-19 vaccination.…”
Section: Accepted Manuscriptmentioning
confidence: 99%